La formación de personalidades éticas: representaciones de sí y moral - Tognetta, Luciene Regina Paulino [UNESP]; Taille, Yves de la (My University, 2011)
The article presents the studies of a current investigation among 75 adolescents from 12 to 15 years old, students of private schools of Campinas city, that have as main objective to notice a possible correspondence among the moral judgements and the representation that individuals have about themselves. From the feeling of admiration the studies bring out the representations of these individuals and answer a questioning if they would have an ethics character or not and if these would correspond to their moral judgements. The results point out to a correspondence among those whose representations of themselves are characterized by more evolved ethics contents and judgements as for sensitivity to the feelings of the characters involved in the situations described. Such studies validate the intention of this article to discuss the correspondences between ethics (how the individual sees himself/herself) and moral (how he/she judges the moral of the situations).

El artículo presenta resultados de una investigación con 75 adolescentes entre 12 a 15 años, estudiantes de colegios privados de la ciudad de Campinas, cuyo principal objetivo fue constatar la posible correspondencia entre los juicios morales y las representaciones que los sujetos tienen de sí mismos. A partir de sentimientos de admiración, la investigación destaca las representaciones de estos sujetos y responde a la pregunta de si tendrían un carácter ético o no y se corresponderían con sus juicios morales. Los resultados apuntan hacia una correspondencia entre aquellos cuyas representaciones de sí se caracterizan por contenidos éticos y juicios más desarrollados, así como por la sensibilidad ante los sentimientos de los personajes que participan en las situaciones descritas. Estos resultados estudios reafirman la intención de este artículo de discutir la correspondencia entre ética (cómo se ve el sujeto) y moral (cómo juzga la moralidad de las situaciones).
The formation of ethical personalities: self-representations and morality
Keywords: Ethics; Virtue; Generosity; Emotions; Self-representation; Ética; virtud; generosidad; emociones; representaciones del sí mismo